Implementasi Pemahaman Keagamaan Guru terhadap Pembinaan Sikap Religius Anak Usia Dini di Yayasan Taman Pendidikan TPQ/RA Wahyu Medan - Dahlia Summayah Sitorus (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
Teachers’ religious understanding plays a vital role in shaping early childhood religious attitudes through systematic, consistent, and contextual guidance. This study aims to analyze the implementation of teachers’ religious understanding in fostering children’s religious attitudes at Yayasan Taman Pendidikan TPQ/RA Wahyu Medan. The research applied a qualitative method with a descriptive approach, using in-depth interviews, observations, and documentation to explore teachers’ experiences in religious nurturing practices. The findings revealed that teachers have successfully integrated religious values into learning activities, such as collective prayers, memorization of short Qur’anic surahs, greeting habits, and prayer exercises. However, challenges remain, including limited use of interactive learning media and low parental involvement in supporting religious habituation at home. These findings imply that teachers’ religious understanding should be enhanced through continuous training and strengthened collaboration with parents to optimize the fostering of children’s religious attitudes. This study contributes to the development of early childhood education, particularly in strengthening character education based on religious values.